STRATEGI KOMUNIKASI PEMASARAN DIGITAL MELALUI MEDIA SOSIAL (Studi Deskriptif Kualitatif Pada Instagram Viar Motor Indonesia) - Ane Jessyca Ramadena; Windhiadi Yoga Sembada; Puri Bestari Mardani (2022)
The mobility of the population in Indonesia is very high, with various types of transportation from land, sea and air, land transportation is the most widely used, especially motorized vehicles. This refers to the data published by the Badan Pusat Statistik in 2019, were 112,771,136 motorized vehicles in Indonesia. From this situation, Viar Motor Indonesia, which is one of the motorcycle manufacturers, sees a high market opportunity. It can be seen in Viar's automotive product sales data, in 2017 along with the use of digital marketing communication strategies. This study aims to determine the digital marketing communication strategy through Instagram social media carried out by Viar Motor Indonesia. The communication model used in this study uses Smith's SOSTAC model and uses the New Media Theory introduced by Pierre Levy. This study uses a qualitative approach with in-depth interviews with relevant sources. The results of this study show that Viar's strategy, tactics, and action stages have been successful. It can be seen that the strategic stage of Viar Motor Indonesia already has the appropriate target audience. At the tactics stage, Viar Motor Indonesia carried out tactics with a message strategy. In the message strategy, Viar uses a creative message strategy. In the action stage, Viar Motor Indonesia runs four digital marketing communication strategies. These stages are carried out in order to create the right marketing communication strategy. Weaknesses can be seen in the control stage in the SOSTAC Model, Viar looks weak or not quite successful because there is content uploaded but there is still something that cannot be understood by the audience.